Gentechnisch modulierte Iodidanreicherung in malignen Tumoren - Haberkorn, Uwe; Askoxylakis, Vasileios; Markert, Annette; Altmann, Annette (Nuklearmedizin, 2010)
After the cloning of the gene encoding the sodium-iodide symporter several trials were made to develop a radioiodine treatment for multiple tumour entities based on NIS gene transfer. These studies revealed in vitro as well as in vivo a tremendous enhancement of iodide accumulation, which was followed by a rapid efflux. Therapy effects were observed in vitro by clonogenic assays and in vivo by growth inhibition of the treated tumours. However, the interpretation of these results were largely different. Problems of radioiodine therapy after NIS transfer are low efficiency of gene transfer and the short exposure time for the tumours caused by the rapid efflux. Trials to enhance therapeutic efficiency by co-transfer of the gene encoding thyroperoxidase failed due to the low enzyme activity.
Gesehen am 09.06.2023